Peran Guru dan Orang Tua dalam Meningkatkan Daya Ingat Anak Usia Dini melalui Permainan Tradisional Edukatif - Siti Rohmah; Opik Hidayat; Iqbal Ramdhoni; Rismawati (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2026)
Memory is one of the essential cognitive abilities that should be developed from an early age because it influences children's learning processes and overall development. However, the development of children's memory requires appropriate and continuous stimulation through activities that are aligned with the characteristics of early childhood. This study aims to analyze the roles of teachers and parents in improving early childhood memory through educational traditional games. The research employed a qualitative approach using a library research method based on journal articles, books, and other relevant scientific literature. Data were collected through literature searching, selection, and documentation, and were analyzed using content analysis techniques to identify themes related to teachers' roles, parents' roles, children's memory, and educational traditional games. The findings indicate that educational traditional games can enhance children's memory, concentration, and attention skills. Teachers play a role in designing and implementing play activities that support learning objectives, while parents provide guidance and reinforcement within the family environment. Effective collaboration between teachers and parents through educational traditional games provides consistent stimulation that supports the optimal development of memory in early childhood.